Philanthropy and social justice in waqf administration in morocco: lessons learnt from the history - Mohamad, Nor Asiah; Mahmud, Fariza; Shahabudin, Syahirah, N; Ahmad, Izham Hakimi; Ismai, Ahmad Fadzil (UNISZA, 2016)
The history of waqf in Morocco dated to as early as 9th century with the creation of waqf education and the establishment of the first on-going university in the world. The creation of Qarawiyyin University as the oldest waqf higher education marks the high quality education system in Islam but sometimes, lacks highlight and appreciation. In Morocco, waqf tradition remains, as social and political obligation and sustainable awareness exist among the notable and common people. Employing a qualitative research method, this paper uses historical institutionalist approach, which include reviewing literatures on history and waqf in Morocco. In addition, the authors engaged in interviews with the officers in charge in order to understand the contemporary administration and the challenges in waqf administration in Morocco. Although waqf has been in practice since the early establishment of the country, the development is relatively firm and steady. Waqf in Morocco works beyond the traditional practices as happens in some Muslim countries. Similar to others, Morocco needs to advance waqf practices in order to fully utilise waqf benefits. Moving along the spirit of waqf in making changes for the Muslim, Malaysia can learn several things progressively even from the past history. Keywords: Waqf, Morocco, waqf education, history, social justice and philanthropy.